A prospective study of efficacy of ultrasound guided transversus abdominis plane block for postcesarean analgesia - Manam, Sravani; Swetha, R. N. V.; Rao, A. S. Kameswara; Murthy, S. G. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The ultrasound guided transversus abdominis plane (TAP) block which provides effective analgesia after lower abdominal surgeries including caesarean section. It is a simple and reliable technique. In this prospective, randomized double-blind study, we determined the efficacy of TAP block using 0.25% Bupivacaine and 0.9N Saline with respect to VAS for pain, postoperative Tramadol consumption and post-operative ondansetron usage. Methods: This study was conducted on 100 adult patients of ASA physical status I and II in the age group of 18 to 40 years undergoing elective lower segment cesarean section under spinal anaesthesia. Study group received TAP block with 0.25% Bupivacaine and control group received 10 ml of 0.9N saline on each side. Patients were analyzed for postoperative pain by pain score (at rest, on movement, on cough) using VAS was recorded at 0, ½, 1, 2, 4, 6, 12 and 24 hours postoperatively. Need for rescue analgesia was assessed by time to first dose of Tramadol requirement and total dose of Tramadol over 24 hours of postoperative period. Ondansetron (4 mg i.v.) was administered whenever nausea score was more than 2 or the patient vomited. All the data was noted using uniform performs. Results: Patients received TAP block with 0.25% Bupivacaine had better pain scores at first hour of postoperative period during rest, cough and movement which was statistically significant (p<0.0010) in comparison to group B. There was a statistically significant difference (p <0.001) in the requirement of total dose of Tramadol as a rescue analgesia in patients who received transversus abdominis block with 0.25% Bupivacaine (138.77 mg) in comparison with other group(240 mg).The mean time to first request for Tramadol was significantly longer in group A (5.8 hrs) in comparison to group B (1.93 hrs) with p value <0.001. Patients received TAP block with 0.9N saline needed more dose of Ondansetron, however, the difference was not statistically significant (p >0.001). Conclusions: TAP block using ultrasound provides substantial reduction in Tramadol consumption, time to first dose of rescue tramadol when compared with control group. This study reinforces the recommendation for TAP as a part of multimodal post-operative analgesic regimen.